2022
DOI: 10.1002/adfm.202205507
|View full text |Cite
|
Sign up to set email alerts
|

Revealing Steric‐Hindrance‐Dependent Buried Interface Defect Passivation Mechanism in Efficient and Stable Perovskite Solar Cells with Mitigated Tensile Stress

Abstract: Interface engineering is one feasible and effective approach to minimize the interfacial nonradiative recombination stemming from interfacial defects, interfacial residual stress, and interfacial energy level mismatch. Herein, a novel and effective steric-hindrance-dependent buried interface defect passivation and stress release strategy is reported, which is implemented by adopting a series of adamantane derivative molecules functionalized with CO (i.e., 2-adamantanone (AD), 1-adamantane carboxylic acid (ADC… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
123
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 119 publications
(137 citation statements)
references
References 39 publications
2
123
0
Order By: Relevance
“…From the FTIR results in Figures 1f and S9, we observed that the stretching vibration of C�O from PbI 2 /EAD shifted toward a lower wavenumber as compared to the EAD molecule, indicating a strong interaction between carbonyl groups in EAD and Pb 2+ . 35,36 Meanwhile, the N−H bonding shifted to a lower wavenumber after mixing PbI 2 and EAD (Figure 1g), demonstrating the formation of N−H•••I hydrogen bonding, which could passivate halide ion defects. 21,37 According to previous reports, ammonium cations may also interact with the Pb−I framework to modulate the growth of perovskite films.…”
Section: Resultsmentioning
confidence: 99%
“…From the FTIR results in Figures 1f and S9, we observed that the stretching vibration of C�O from PbI 2 /EAD shifted toward a lower wavenumber as compared to the EAD molecule, indicating a strong interaction between carbonyl groups in EAD and Pb 2+ . 35,36 Meanwhile, the N−H bonding shifted to a lower wavenumber after mixing PbI 2 and EAD (Figure 1g), demonstrating the formation of N−H•••I hydrogen bonding, which could passivate halide ion defects. 21,37 According to previous reports, ammonium cations may also interact with the Pb−I framework to modulate the growth of perovskite films.…”
Section: Resultsmentioning
confidence: 99%
“…Regarding the buried interface stress and defect, Chen et al adopted adamantane-derivative molecules with CO functional groups to tune the steric hindrance of chemical interaction at the SnO 2 /perovskite interface, which effectively passivated the interfacial defect and mitigated the interfacial strain. 189 In addition, the ionic motion induced by an electric field resulted in increased interfacial lattice strain and even collapse of the structure, which was directly related to the stability. 190 Adopting a fullerene derivative to release the interface strain could effectively inhibit the formation of interface defects and enhance the structure stability (Fig.…”
Section: Strategies To Enhance Stabilitymentioning
confidence: 99%
“…41,42 It should be noted that residual tensile stress is an factor affecting the stability of perovskite films. 27 In contrast, the GIXRD peaks of the DDSI 2 perovskite film (Figure S17b) show a trend toward higher angles by a change in φ and the corresponding slope becomes positive (Figure S17c). This result implies that DDSI 2 modification can effectively alleviate the residual stress, improving the longterm stability of PSCs.…”
mentioning
confidence: 99%
“…Furthermore, the 2θ sin 2 φ method was employed to examine the surface residual stress state of the perovskite films. , For pristine perovskite films (Figure S17a), the characteristic diffraction peaks show a shift to lower angles with φ from 10 to 60°, indicating that the interplanar spacing gradually increases according to Bragg’s law . The negative slope of the linear fit of 2θ sin 2 φ shows the tensile stress of the pristine perovskite (Figure S17c), consistent with previous reports. , It should be noted that residual tensile stress is an factor affecting the stability of perovskite films . In contrast, the GIXRD peaks of the DDSI 2 perovskite film (Figure S17b) show a trend toward higher angles by a change in φ and the corresponding slope becomes positive (Figure S17c).…”
mentioning
confidence: 99%
See 1 more Smart Citation